2021
DOI: 10.1002/aoc.6194
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and anticancer activity of new binuclear complexes of 2,2′‐malonylbis(N‐phenylhydrazine‐1‐carbothioamide)

Abstract: The bimetallic complexes of 2,2′‐malonylbis(N‐phenylhydrazine‐1‐carbothioamide) have been prepared and characterized by elemental and spectral analyses. The free ligand exists in keto‐thione form, whereas in complexes it chelated to the metal ion in binegative tetradentate and neutral tetradentate manners. The electronic spectra and magnetic moment measurements showed that all the complexes have an octahedral geometry except the [Cu2(H2L)(OAc)2]EtOH complex which has square planar structure supported by the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…On the other hand, the spectrum of Zn(II) complex, in DMSO - d 6 , showed a singlet signal at 13.98 ppm that was designated to the free phenolic proton (OH) [ 29 , 30 ]. The other singlet signal at 8.59 ppm was ascribed to the azomethine proton (HC=N) [ 42 , 50 ]. The appearance of only one signal due to the phenolic OH proton confirmed that it is free, no H-bond or metal binding, and the downfield shift of azomethine proton supported the participation of these groups in bonding to metal ion [ 42 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the spectrum of Zn(II) complex, in DMSO - d 6 , showed a singlet signal at 13.98 ppm that was designated to the free phenolic proton (OH) [ 29 , 30 ]. The other singlet signal at 8.59 ppm was ascribed to the azomethine proton (HC=N) [ 42 , 50 ]. The appearance of only one signal due to the phenolic OH proton confirmed that it is free, no H-bond or metal binding, and the downfield shift of azomethine proton supported the participation of these groups in bonding to metal ion [ 42 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The other singlet signal at 8.59 ppm was ascribed to the azomethine proton (HC=N) [ 42 , 50 ]. The appearance of only one signal due to the phenolic OH proton confirmed that it is free, no H-bond or metal binding, and the downfield shift of azomethine proton supported the participation of these groups in bonding to metal ion [ 42 , 50 ]. The spectrum displayed the other bands at more or less the positions (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…DFT method is one that conveys the chemical reactivity as well as the site selectivity of molecular systems. The energies of the frontier molecular orbitals (EHOMO, ELUMO) (figs.9-12 C & D), the energy band gap which explains the eventual charge transfer interaction within the molecule, electronegativity (v), chemical potential (l), global hardness (g), global softness (S) and global electrophilicity index (x) [39] are evaluated according to literature [40] and the data recorded in Table 6. This new reactivity index measures the stabilization in energy when the system acquires an additional electronic charge from the environment.…”
Section: 8dft Studymentioning
confidence: 99%